Chemical syntheses and in vitro antibacterial activity of two desferrioxamine B-ciprofloxacin conjugates with potential esterase and phosphatase triggered drug release linkers - Ji, Cheng (2012)
Two desferrioxamine B-ciprofloxacin conjugates with “trimethyl-lock” based linkers that are designed to release the antibiotic after esterase or phosphatase-mediated hydrolysis were synthesized. The potential esterase-sensitive conjugate 13 displayed moderate to good antibacterial activities against selected ferrioxamine-utilizing bacteria, although the activities were lower than the parent drug ciprofloxacin. However, the potential phophatase-sensitive conjugate 23 was inactive against the same panel of organisms tested. These properties appeared to be related to the activating efficiency of the linker by the enzyme and to the outer membrane protein recognition of the chemically modified siderophore used in the conjugate.